The Influence of Teaching Experience, School Culture and Motivation on Teacher Performance - Fitriah ULFA; Zahara Tussoleha RONY; Sugeng SUROSO (International Journal of Environmental, Sustainability, and Social Science, 2022)
Teacher performance is an essential element in the world of education which is a determinant of the high or low quality of education that occurs in the school environment, this is because teachers are people who often interact with students directly during the teaching process. The purpose of this research is to know how much the influence of teaching experience, school culture and motivation can affect teacher’s performance. The data analysis method is quantitative, Partial Least Squares (PLS) is the data analysis approach used in this study. Partial Least Squares (PLS) is a Structural Equation Modeling (SEM) equation model that utilizes component-based structural equation modeling techniques.. The sampling technique used in this research is a Saturated Sample. The samples taken were 71 samples of MTS 1 teachers in Bekasi City. This study uses PLS 3 as an analytical tool and is assisted by the Statistical Package for the Social Sciences or SPSS. The partial test results showed that teaching experience significantly affected teacher performance, school culture had no significant effect on teacher performance, and motivation significantly affected teacher performance. The results of the simultaneous test study showed that teaching experience, school culture, and motivation had a significant effect on teacher performance.